Analisis Dampak Fatherless Terhadap Perkembangan Sosial Remaja di SMKN 3 Padang - Zubaidah Sandy; Linda Fitria; Yuliawati Yunus (Yayasan Citra Dharma Cindekia, 2024)
This research aims to analyze the impact of fatherlessness on adolescent social development. The method used in this research is quantitative descriptive correlational. The research was conducted at SMKN 3 Padang class XI. The population in this study was 464 people with a sample of 46 respondents. The sampling technique is non-random. The instrument in this research is a Likert scale questionnaire. Data analysis was carried out using statistical programs on the computer IBM Statistics 20.0 and Microsoft Excel 2010. Based on the results of data processing, the rcount value was obtained, namely -0.509, while the rtable value was 0.290 because the rcount value was smaller than the rtable value (-0.509 <0.290), it was concluded that The impact of fatherlessness does not affect teenagers' social development.